2010
DOI: 10.1021/ol1007586
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-Aryl and N-Alkyl Anthranilic Acids via SNAr Reaction of Unprotected 2-Fluoro- and 2-Methoxybenzoic Acids by Lithioamides

Abstract: Substitution of the fluoro or methoxy group in unprotected 2-fluoro- and 2-methoxybenzoic acids to afford N-aryl and N-alkyl anthranilic acids occurs upon reaction with lithioamides under mild conditions in the absence of a metal catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…However, diisopropylamine (2d) with large steric hindrance was proved not feasible to undertake the S N Ar reaction, which was inconsistent with the previous reports. 19 Furthermore, cycloalkyl amine could fuse with 1a albeit with moderate to excellent isolated yields, for example pyrrolidine (3k, 80%), piperidine (3l, 86%), morpholine (3m, 91%), azetidine (3n, 43%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, diisopropylamine (2d) with large steric hindrance was proved not feasible to undertake the S N Ar reaction, which was inconsistent with the previous reports. 19 Furthermore, cycloalkyl amine could fuse with 1a albeit with moderate to excellent isolated yields, for example pyrrolidine (3k, 80%), piperidine (3l, 86%), morpholine (3m, 91%), azetidine (3n, 43%).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we designed and screened two special substrates to evaluate the electronic effect on the benzoxazole fragment (1h, 1i), which demonstrated that neither electron-withdrawing nor electrondonating group on benzo[d]oxazole ring would affect the S N Ar efficiency of this reaction, both smoothly converted into substituted products (3s, 94%; 3t, 90%; 3u, 94%). Interesting, 3u was generated and fused with two imidazole molecules, one imidazole molecule was fused the standard C−F bond, while another is, determined by 19 F NMR spectra, the C−F bond ortho to oxygen atom of benzoxazole fragment (see Supporting Information). After all, we want to shed some light on the reaction mechanism.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In 2010, Mortier and co-workers described a nucleophilic substitution of 2-methoxybenzoic acid (1) using in situ prepared lithium amides to give anthranilic acids 3 with low to excellent efficacy (14-97% yield, Scheme 2). 17 This strategy avoids the use of protection/deprotection operations for the carboxy group. Furthermore, N-aryl-and N-alkylanthranilic acids are very important synthetic blocks found in anti-inflammatory agents and candidates for therapy in neurodegenerative and amyloid diseases.…”
Section: Short Review Synthesismentioning
confidence: 99%
“…Most of these methods have certain limitations such as tedious processes, harsh reaction conditions, application of hazardous catalysts, generation of toxic metal reagents, and low yields of products. Additionally, in view of the pharmaceutical application of arylbenzimidazoles and due to potentially toxic contamination of pharmaceutical products, effective removal of some metals such as Pd or Cu in active pharmaceutical ingredients (API) provides important health benefits [19]. So, it has been worthwhile to search for practical metal-free conditions.…”
Section: (Fig)mentioning
confidence: 99%